IFPRI's approach to research - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The International Food Policy Research Institute provides research-based policy solutions to sustainably reduce poverty and end malnutrition in low-and middle-income countries and has played a vital role in informing policies, programs, and investments since its founding in 1975. This document provides a brief introduction to IFPRI and sets out how we approach our research, along with the scope of our current work.